Pengaruh Suasana Lingkungan dan Kenyamanan terhadap Kepuasan Wisatawan di Pantai Viovio Batam - Surya Rahman Hakim; Agung Edy Wibowo; I Wayan Thariqy Kawakibi Pristiwasa; Nensi Lapotulo (Lembaga Pengembangan Kinerja Dosen, 2026)
Marine attractions like Viovio Beach in Batam are a big part of the tourism industry, which is a vital part of regional economies. How pleasant and relaxing the surrounding area is has a significant impact on how satisfied tourists are. Examining how the natural setting and amenities at Viovio Beach affect visitors' happiness is the primary goal of this research. With the use of questionnaires sent out to 150 participants, a descriptive and quantitative approach was used. Multiple regression tests, as well as tests for validity and reliability, classical assumptions, and SPSS, were used to analyze the data. Tourist satisfaction is partly and concurrently impacted by environmental ambiance and comfort, according to the results. With an Adjusted R² value of 0.677, these factors explain 67% of the variation in satisfaction, with comfort being the most important component. The findings show that cleanliness, safety, and helpful staff are the three most important factors in creating memorable experiences for tourists. According to the research, if you want your location to be more competitive and promote sustainable tourism, you need to focus on making the atmosphere more comfortable and pleasant.